The Margaridation of Household Accounting by Patriacial Ideology: A Phenomenological Study - Fansyuri, M Iqbal; Sokarina, Ayudia (E-Jurnal Akuntansi, 2025)
This study aims to explore the meaning of household accounting using an interpretive paradigm and a phenomenological approach. Data were collected through in-depth interviews with individuals who have lived a household. Data analysis was carried out through the stages of Noema, Epoche, Noesis, Intentional Analysis, and Eidetic Reduction. The results of the study indicate that household accounting practices are marginalized due to the dominance of patriarchal ideology that places men as the main authority holders in the family. Based on the reflective awareness of informants, household accounting has two meanings: material and immaterial. The material meaning refers to the double burden of housewives in managing finances and domestic work, while the immaterial meaning includes psychological pressure, limitations in decision-making, and belief in sustenance from God. This study contributes to the development of accounting theory by showing that household accounting is a practice that is full of ideological values, so it reflects more social and emotional pressure than just a technical tool for financial management and decision-making. Keywords: Household Accounting; Phenomenology; Accounting Ideology; Financial Management.